Constituição da identidade profissional docente no curso de Pedagogia a partir do estágio supervisionado - SOUZA, Angelita de Fátima (2015)
This research is related to the issue of the constitution of professional identity in teachers training. The study was guided by the issue: In what way the supervised apprenticeship helps the identity formation of the future teacher in Pedagogy courses? It had as a main goal to understand how students from Pedagogy courses are constituting themselves as teachers, from the supervised training. Theoretical references used about teachers profession and professionalism are based on discussions from Bordoncle, Roldão, Boing, among others; concerning identity, it was based on Dubar and Bolívar works, and related to teachers knowledge we dialogued with Tardif. It is a nature-based, qualitative research, guided by bibliographical and documental study, field research, having as a methodological theoretical reference the studies of Bodgan and Biklen, Ludke and André, Flick, André and Cellard. Instruments used to produce data were questionnaire, semi-structured interview, apprenticeship reports, political-pedagogical project, field diary and search on internet sites. For data analysis it was used the Excel program, documental analysis and prose analysis. The field investigated was the Pedagogy course from Uberaba city, Minas Gerais state, in a classroom format. Subjects of the research are students from the course mentioned above, who were attending the supervised apprenticeship, related to the Elementary School I. For analysis, it was used data concerning three interns, revealing that the constitution of the teacher identity occurs in different contexts and that the process of observation and reflection on actions, which guide the school context, contribute to this constitution. Also, constitutive elements of the intern’s teacher identity are: 1) perception of the theory-practice relationship, that there is neither theory without practice nor practice without a theory to justify it; 2) how they consider the fundamental apprenticeship in their formation and the necessity of continued education, including that one started before the end of graduation. At last, it is worth highlighting some challenges which still permeate teachers formation: need of supervision follow-up by the university professor, as well as the recognition by the school, teacher from the school, the student as an intern, as a learner who deserves respect; the strengthen of the university-school relationship.